992 EVALUATION OF MYOCARDIAL WORK INDEX IN PREDICTING IN-HOSPITAL COMPLICATION IN PATIENTS WITH TAKOTSUBO SYNDROME. (15th December 2022) - Migliarino, Serena; Cristiano, Mario; Iuliano, Giuseppe; Ferruzzi, Germano Junior; Loria, Francesco; Bellino, Michele; Silverio, Angelo; Attisano, Tiziana; Baldi, Cesare; Ciccarelli, Michele; Galasso, Gennaro; Vecchione, Carmine; et al.
Abstract: Backgrounds: Tako-tsubo syndrome (TTS) is a reversible heart failure pathology characterized by transient myocardial left ventricular (LV) dysfunction. Although traditionally considered a benign condition in-hospital complications are frequent in this cohort. Non-invasive myocardial work (MW) parameters are considered as emerging indexes in evaluating global and regional myocardial systolic function. Objective: to investigate the potential association of MW compared to standard echocardiography parameters, such as LV ejection fraction (EF) with in-hospital complications, in TTS patients. Methods: thirty-eight patients (mean age, 68 ± 12 years, 35 women) with TTS diagnosed with Takotsubo Italian Network criteria were prospectively enrolled and underwent a transthoracic Doppler echocardiography within 24 hours from hospital admission. MW is derived from the non-invasive strain-pressure loop obtained from the 2D strain data, integrating into its calculation the non-invasive brachial arterial pressure. Constructive MW (CMW), MW index (MWI), MW efficiency (MWE), and wasted myocardial work (WMW) were measured. In hospital complications (HC) were defined as a composite of apical LV thrombosis, hypokinetic arrhythmias (HA), supraventricular tachycardia (SVT), acute heart failure (AHF), ventricular tachycardia/fibrillation (VT/VF), cardiogenic shock (CS), respiratory arrest (RA), stroke and cardiac death (CD). The normal values ​​for the echocardiographic parameters are reported in the Table. Odds ratio, sensitivity and specificity were used to quantify the ability of EF and MW (abnormal vs normal values) in predicting HC. Results: HC occurred in 16 TTS patients (26% with AHF; 10% with SVT; 8% with CS; 5% with apical LV thrombosis; 5% with HA; 2, 6% with RA; 2, 6% with stroke; 2% with VT/VF). The MWI and CMW parameters appear to have the best performance in predicting in-hospital complications (odds ratio for having HC: 10.4 (95% confidence interval: 1.2 to 93.3); 8.6 (0.9 to 77.6) respectively, Table), followed by EF (odds ratio 7.0 (0.8 to 64.1)) and WMW (odds ratio 4.8 (0.9 to 26.7)). MWI has the same sensitivity (94%) as CMW and EF, but higher specificity (41% vs 32%). Of note, the highest specificity was obtained by the WMW parameter (41%). Conclusion: global and regional myocardial performance is transiently impaired in TTS and significantly associated with HC. Although limited by the low number of patients, these results suggest that myocardial work parameters have a good sensistivity and may have a better performance than the EF value in predicting intra-hospital complications. Larger studies will be necessary to confirm these preliminary results.